Analisis Dampak Lingkungan dan Implikasi Ekonomi Aktivitas Pembangkit Listrik Tenaga Panas Bumi (PLTP) dalam Mewujudkan Sustainable Development Goals (SDGs) di Indonesia - Dinda Permata Sari (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Geothermal Power Plants (PLTP) are one of the renewable energy sources with great potential to support the clean energy transition in Indonesia. However, PLTP activities also have environmental impacts that need to be comprehensively assessed to ensure both economic and ecological sustainability. This study aims to analyze the environmental impacts and their economic implications in achieving the Sustainable Development Goals (SDGs). The research employs a qualitative approach through literature studies sourced from scientific journals, official reports, and energy policy documents. The results indicate that although PLTP reduces carbon emissions by up to 90% compared to fossil-fueled plants, its activities still pose environmental risks such as land-use changes, water pollution, and biodiversity loss. On the other hand, PLTP provides economic benefits through job creation, increased regional income, and national energy diversification. Therefore, an integrated mitigation strategy involving environmental policy, technological efficiency, and investment planning based on Life Cycle Cost (LCC) is required to ensure that PLTP truly contributes to the green economy and sustainable development.